Ezrin Peptide Therapy from HIV to COVID: Inhibition of Inflammation and Amplification of Adaptive Anti-Viral Immunity - Rupert D. Holms (MDPI AG, 2021)
Human Ezrin Peptides (HEPs) are inhibitors of expression of IL-6 and other inflammatory cytokines, amplifiers of adaptive B cell and T cell immunity and enhancers of tissue repair. The mutation stable C-terminus of HIV gp120, mimics 69% of the “Hep-receptor”, a zipped α-helical structure in the middle of the α domain of human ezrin protein. Synthetic peptides homologous to the Hep-receptor of ezrin of five to fourteen amino acids, activate anti-viral immunity against a wide range of viruses (HIV, HCV, herpes, HPV, influenza and other human respiratory viruses). Human Ezrin Peptide One (HEP1) TEKKRRETVEREKE (brand name Gepon, registered for human use in Russia from 2001) is a successful treatment for opportunistic infections in HIV-infected patients. That treats HEP1and prevents mucosal candidiasis, herpes zoster outbreaks and infection-induced chronic diarrhea. There are clinical publications in Russian on the successful treatments of chronic recurrent vaginal candidiasis, acute and chronic enterocolitis and dysbacteriosis, which are accompanied by normalization of the mucosal microbiome, and the decline or disappearance of inflammation. HEP1 is also an effective treatment and prevention for recurrent inflammation and ulceration in the stomach, duodenum and colon. HEP1 and RepG3 GEKKRRETVEREGG (a derivative of HEP1) have been used successfully as an inhaled spray peptide solution to treat a small number of human volunteers with mild-to-moderate COVID, resulting from SARS-CoV-2 infection, based on earlier successes in treating acute viral respiratory disease with inflammatory complications. Ezrin peptides seem to correct a dysregulation of innate immune responses to SARS-CoV-2. They are also adjuvants of B cell adaptive immunity and increase antibody titres, resulting in protection from lethal virus infection of mice. In a clinical study in Moscow, orally administered HEP1 was shown to enhance antibody-titres produced in response to hepatitis-B vaccination. These very preliminary but promising results with ezrin peptide treatment of COVID must be replicated in large-scale randomised placebo controlled clinical studies, to be verified.